(untitled) (Global Journal of Management and Business Research, 2019)
The education process in higher school is now become a big concern especially dealing with the students on its environmental setting. The main concern is related to the commitment, satisfaction, and performance/ achievements of students which support the college climate as expected. Regarding this topic, it is necessary to conduct research to see the level of students’ commitment, satisfaction, and performance/ achievements, particularly at Economics College STIE Galileo Batam. Therefore, this study focuses on this topic of investigation. This research is quantitative research involving 33 respondents taken from students who studied at STIE Galileo. The purpose of this study was to look at the stages of commitment, satisfaction, performances/ achievement of students at STIE Galileo. The research data was collected through a questionnaire which was then processed using SPSS statistics. The descriptive frequency analysis and Mean Score were directed to see the levels of students’ commitment, satisfaction, and performance/ achievement. The descriptive analysis result shows that the commitment and satisfaction are in the high category level, while the students’ performance/ achievement is in the level of both good and very good category.